Nanocompósitos híbridos modificados com nanotubos de carbono: síntese e caracterização - Gláucio Carley Pereira (2013)
In this work were developed nanocomsites reinforced with carbon nanotubes (CNTs) in the form of multiple wall interlaminar and intralaminar also. We tried to, with this procedure, an improvent in the mechanical properties of these composites. The matrix used was a combination of carbonfiber and glass and epoxy resin. The methods of adding CNTs to this array are: direct deposition on the fibers in the resin dispersion and also epóxi. This study was conducted on composites with and without central holes for ascertainig the effect of strain concentrators. SEM images showed good adhesion of nanotubes of matrix composites, as well as Raman spectroscopy. There was a significant improvement in stiffness of composites with CNTs deposited (on average 240% in nanocomposites with about 60 mg of CNTs). The best results of increased tensile strnght, maximum strian supportes and yield strin were obtained with the samples produced with resin nanomodificada with 0,3% carbon nanotubes by weight, when this resin was added only in the central interfaces of these composites. Increase of 84,75% for maximum strain and 64,96% for the yield strain.